Gli uomini e le cose: I. Figure di restauratori e casi di restauro in Italia tra XVIII e XX secolo. Atti del Convegno Nazionale di Studi (Napoli, 18-20 aprile 2007) Men and things: I. Restorers and restorations in Italy between the 18th and 20th centuries. Proceedings of the National Conference, Naples, 18-20 April 2007 - Paola D'Alconzo (Clio: Saggi di scienze storiche, archeologiche e storico-artistiche, 2007)
The essays collected in this volume revolve around the activities of protection and preservation of the historical-artistic and archaeological heritage promoted in Italy between the second half of the 18th century and the first half of the 20th. They refer to different works in both chronology and materials analyzed (wall and gallery paintings, medieval and Renaissance sculptures, mosaics, excavated vases, entire archaeological sites), with the natural corollary of the theoretical debates and the methodological statements that accompanied these same works. The reference to Fernand Braudel in the title embodies the desire to trace a path that is not abstract, but grounded in the reality of the objects and of those who have been studying them in the past. The choice of a relatively broad time span, as well as the decision not to focus exclusively on a single type of object, seek to highlight the diachronic evolution of general concepts such as conservation and restoration, understanding links and differences between the pre-and post-unification phases of the layered national landscape. Further, they aim to retrace the conservative history of these works, hoping to also provide an interpretative tool to those who, in charge of the protection of these works, are tasked with the planning of future interventions: a proper programmatic preservation cannot, in fact, ignore the historical dimension that needs to inform any study that is to be done today on these works.